Sarcolemmal ATP-sensitive K(+) channels control energy expenditure determining body weight - Alekseev, Alexey E. (2010)
Metabolic processes that regulate muscle energy use are major determinants of bodily energy balance. Here we find that sarcolemmal ATP-sensitive K(+) (K(ATP)) channels, which couple membrane excitability with cellular metabolic pathways, set muscle energy expenditure under physiological stimuli. Disruption of K(ATP) channel function provoked, in conditions of unaltered locomotor activity and blood substrate availability, an extra energy cost of cardiac and skeletal muscle performance. Inefficient fuel metabolism in K(ATP) channel-deficient striated muscles reduced glycogen and fat body depots promoting a lean phenotype. The propensity to lesser body weight imposed by K(ATP) channel deficit persisted under a high-fat diet, yet obesity restriction was achieved at the cost of compromised physical endurance. Thus, sarcolemmal K(ATP) channels govern muscle energy economy, and their down-regulation in a tissue-specific manner could present an anti-obesity strategy by rendering muscle increasingly thermogenic at rest and less fuel efficient during exercise.